MIXING DEVICE, METHOD FOR MIXING, AND METHOD FOR CLEANING A MIXING DEVICE - SCHMIDT UWE; PAASCHE CHRISTIAN KARL (2020)
The present invention relates to a mixing device (1), especially for mixing solids in a mixing vessel (2), comprising a stirring element (4) having at least two helical stirrer blades (7, 8) connectedto a motor-driven shaft (5), wherein the stirrer blades (7, 8) have a first portion (10), a second portion (11) and a third portion (12), every one of these portions (10, 11, 12) has a constant gradient (m1, m2, m3) of one steepness or a gradient (m1, m2, m3) which is different from the constant gradient and has a curvature, and at least one of the constant gradients (m1, m2, m3) has a steepnessdifferent from the at least one other constant gradient (m1, m2, m3), or one of the different gradients (m1, m2, m3) has a curvature that is different from the at least one other different gradient (m1, m2, m3). 本发明涉及一种混合装置(1)，尤其是用于混合在混合容器(2)中的固体，该混合装置具有搅拌机构(4)，该搅拌机构具有至少两个螺旋形构造的搅拌叶片(7，8)，所述搅拌叶片与能以马达驱动的轴(5)连接，其中，搅拌叶片(7，8)具有第一区段(10)、第二区段(11)和第三区段(12)，其中，这些区段(10，11，12)中的每个区段具有恒定的斜坡(m1，m2，m3)或与恒定的斜坡有差别的斜坡(m1，m2，m3)，所述恒定的斜坡具有陡度